Temporal transcriptome and metabolome study revealed molecular mechanisms underlying rose responses to red spider mite infestation and predatory mite antagonism - Cai, Yanfei; Shi, Ziming; Zhao, Peifei; Yang, Yingjie; Cui, Yinshan; Tian, Min; Wang, Jihua (Frontiers in Plant Science, 2024)
Introduction Red spider mite (Tetranychus urticae) infestation (SMI) is a detrimental factor for roses grown indoors. Although predatory mite (Neoseiulus californicus) antagonism (PMA) is often utilized to alleviate SMI damage, little is known about the defensive response of greenhouse-grown roses to SMI and the molecular mechanism by which PMA protects roses. Methods To determine the transcriptome and metabolome responses of roses to SMI and PMA, the leaves of a rose cultivar (“Fairy Zixia/Nightingale”) were infested with T. urticae, followed by the introduction of predator mite. Leaf samples were collected at various time points and subjected to transcriptome and metabolome analyses. Results We found that 24 h of SMI exerted the most changes in the expression of defense-related genes and metabolites in rose leaves. KEGG pathway analysis of differentially expressed genes (DEGs) and metabolites revealed that rose responses to SMI and PMA were primarily enriched in pathways such as sesquiterpenoid and triterpenoid biosynthesis, benzoxazinoid biosynthesis, stilbenoid, diarylheptanoid and gingerol biosynthesis, phytosterol biosynthesis, MAPK signaling pathway, phenylpropanoid biosynthesis, and other pathways associated with resistance to biotic stress. Rose reacted to SMI and PMA by increasing the expression of structural genes and metabolite levels in phytosterol biosynthesis, mevalonate (MVA) pathway, benzoxazinoid biosynthesis, and stilbenoid biosynthesis. In addition, PMA caused a progressive recover from SMI, allowing rose to revert to its normal growth state. PMA restored the expression of 190 essential genes damaged by SMI in rose leaves, including transcription factors DRE1C, BH035, MYB14, EF110, WRKY24, NAC71, and MY108. However, after 144 h of PMA treatment, rose responsiveness to stimulation was diminished, and after 192 h, the metabolic levels of organic acids and lipids were recovered in large measure. Conclusion In conclusion, our results offered insights on how roses coordinate their transcriptome and metabolome to react to SMI and PMA, therefore shedding light on how roses, T. urticae, and N. californicus interact.